Revision of the Australian millipede genus Pogonosternum Jeekel, 1965, with descriptions of two new species (Diplopoda, Polydesmida, Paradoxosomatidae) - Decker, Peter; Mesibov, Robert; Voigtländer, Karin; Xylander, Willi E.R. (European Journal of Taxonomy, 2017)
The southeastern Australian millipede genus Pogonosternum Jeekel, 1965 is revised. Pogonosternum nigrovirgatum (Carl, 1902), P. adrianae Jeekel, 1982 and P. laetificum Jeekel, 1982 are redescribed; P. jeekeli Decker, sp. nov. and P. montanum Decker, sp. nov. are described from Victoria, New South Wales and Tasmania. P. nigrovirgatum infuscum Jeekel, 1982 and P. coniferum Jeekel, 1965 are junior synonyms of P. nigrovirgatum (Carl, 1902). An updated key to all five species of the genus is presented.